ETIOLOGI, DAMPAK DAN MANAJEMEN EARLY CHILDHOOD CARIES (ECC) - Astuti, Eko Sri Yuni (Interdental: Jurnal Kedokteran Gigi, 2020)
Early childhood caries (ECC) is one of the most prevalent diseases in children worldwide. Streptococcus Mutans is the main bacteria that have a strong association with ECC, and these bacteria can be transmitted from mother to child. ECC does not only affect children’s oral health but also the general health of the children and the end affects their quality of life. The impacts of ECC such as problems with sleeping, speaking eating, premature loss of primary dentition, and this condition often leads to orthodontic problems in adult life. Management of ECC has begun preventive strategies, curative and rehabilitative treatment also. As we know the etiology and management of ECC, the impact can be avoided, and the children still have a good quality of life.